Development and performance evaluation of herbicide applicator as an attachment to the paddy transplanter - ANEESH PAPPAN D JIYA C. VARGHESE SANDEEP KUMAR; Dr. Jayan P. R (Guide) (Tavanur 2012 Department of Farm Power Machinery and Energy)
Development and performance evaluation of herbicide applicator as an attachment to the paddy transplanter
Development and performance evaluation of herbicide applicator as an attachment to the paddy transplanter